Least-squares construction of the yield curves for Italian government securities, 1957-1967. Part II - MASERA, R.S. (PSL Quarterly Review, 2014)
This is the second part of a study on the least-squares construction of the yield curves for Italian government securities from 1957 to 1967, in which the author considers the technical aspects. Some general considerations are made before the free-hand interpolation of Durand’s “basic yields” and the U.S. treasury securities curves is considered. The linear interpolation of Grant’s British government securities yield curves is then assessed. Finally, the method for least-squares interpolation is explained before the regression model used for Italian B.T.P. and the resulting estimated yield curves are presented. JEL: G12, H63, E43